2004
DOI: 10.1155/s1110724304308119
|View full text |Cite
|
Sign up to set email alerts
|

Serial Analysis of Gene Expression: Applications in Human Studies

Abstract: Serial analysis of gene expression (SAGE) is a powerful tool, which provides quantitative and comprehensive expression profile of genes in a given cell population. It works by isolating short fragments of genetic information from the expressed genes that are present in the cell being studied. These short sequences, called SAGE tags, are linked together for efficient sequencing. The frequency of each SAGE tag in the cloned multimers directly reflects the transcript abundance. Therefore, SAGE results in an accur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…16 Its main advantage over other methods is that it does not require prior knowledge of the genes of interest and provides qualitative and quantitative data of potentially every transcribed sequence in a particular cell or tissue type. 16 SAGE has the capability of detecting and quantifying the expression of large numbers of known and unknown transcripts 11 and has been demonstrated to be reproducible. 61 The computer program SAGEana was used to analyze the NHMC and HMCL libraries to eliminate artifacts and to adequately treat the replicated ditags.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Its main advantage over other methods is that it does not require prior knowledge of the genes of interest and provides qualitative and quantitative data of potentially every transcribed sequence in a particular cell or tissue type. 16 SAGE has the capability of detecting and quantifying the expression of large numbers of known and unknown transcripts 11 and has been demonstrated to be reproducible. 61 The computer program SAGEana was used to analyze the NHMC and HMCL libraries to eliminate artifacts and to adequately treat the replicated ditags.…”
Section: Discussionmentioning
confidence: 99%
“…15 The SAGE method has also been used in a wide variety of applications such as analysis of the effect of drugs on tissues or disease-related genes and gaining insights into disease pathways. 16 A few SAGE analyses of retinal tissue have been conducted during the past few years. Blackshaw et al 17 were the first ones to study the mouse retina by SAGE, followed with a SAGE analysis of each cell type involved in mouse retinal development including Müller cells.…”
mentioning
confidence: 99%
“…Both the constructed transcript sets for Drosophila melanogaster and Caenorhabditis elegans and their associated tag mappings are available from http://sage.bcgsc.ca//tagmapping/. (39) General applications of SAGE Since the discovery of SAGE several years ago, it has been used to provide a comprehensive analysis of a variety of (42) In addition to these systems, SAGE technology has been used to study gene expression in various types of cancer and during tumor formation. (43) These studies resulted in the identification of tumor-specific markers, transcriptional pathways, or therapeutic targets.…”
Section: Databases Of Sage Datamentioning
confidence: 99%
“…Currently, the molecular pathology of GBM and its correlation to behavior are not well known; many molecular aberrations detected in GBM may have diagnostic and/or prognostic implications. Amplification of oncogenes such as the epidermal growth factor receptor (EGFR) [5,[9][10][11], as well as loss of tumor suppressors like PTEN, p53, or p16/INK4A are some of the most common genetic alterations in GBM [12][13][14]. It was recently reported that isocitrate dehydrogenase (IDH1) mutations and MGMT hypermethylation are associated with the prognosis of GBM [15][16][17].…”
Section: Introductionmentioning
confidence: 99%